Perancangan Mesin Pemipil Jagung Ekonomis, Aman dan Efisien Menggunakan Metode Vdi 2221 (Verein Deutscher Ingenieure) - Chandrahadinata, Dody; Taptajani, Dedi Sa'dudin; Suherman, Toni Hari (Jurnal Kalibrasi, 2025)
This corn sheller machine will be discussed as an effective and safe tool to perform the task of shelling corn at a low production cost, safely, and economically affordable. This machine can help farmers shell maize with cheap or unused materials, reduce time and effort, and optimize the use of resources, resulting in better economic returns. Not much research has been done in Indonesia that looks at how to make an efficient, cost-effective, and safe maize sheller machine. To make an efficient, cost-effective, and safe corn sheller machine, this research uses the VDI 2221 method. The focus of her research was smallholder farmers who face geographical challenges and limited resources. The machine was made using inexpensive items such as wood, V-belt, 125 Watt Shimizu PS 128 BIT electric motor, and 2-inch pipe. Economic, safety, and efficiency analysis were conducted for the validation of the machine.Anthropometry is a tool to measure body size.